Stakeholder attitudes towards donating and utilizing donated human breastmilk - Lubbe, Welma; Oosthuizen, Charlene S.; Dolman, Robin S.; Covic, Namukolo (MDPI, 2019)
The promotion and support of human milk banks (HMBs) can enhance exclusive breastfeeding rates. The success and sustainability of HMBs depend on the support from relevant healthcare workers and related communities. This study aimed to determine attitudes of key stakeholders, including mothers, healthcare workers and grandmothers, regarding the donation and receipt of human breastmilk. This study was conducted at a public hospital and clinics in the North West Province, South Africa. Eight focus group discussions explored the attitudes regarding donating and receiving human breastmilk: three groups with mothers of infants (n = 13), three with grandmothers (>60 years old) (n = 17) and two with healthcare professionals working with infants (n = 11). Four main themes emerged: perception regarding breast and formula feeding; exposure to the concept of “wet nursing”; breastmilk donation; and utilization and opinions of community members and traditional healers. Specific barriers identified included the processes for donating and receiving milk, safety, human immuno-deficiency virus (HIV) screening and cultural beliefs. Mothers’ fears included having insufficient milk for their own infants, changes in the quality of donated milk during pasteurization and transportation and HIV transmission. Despite barriers towards donations to and the use of HMBs, sufficient information could enhance donations by mothers and breastmilk utilization.